Treatment With FoxP3+ Antigen-Experienced T Regulatory Cells Arrests Progressive Retinal Damage in a Spontaneous Model of Uveitis - Liu, Yi-Hsia; Mölzer, Christine; Makinen, Kimmo; Kamoi, Koju; Corbett, Clare L. C.; Klaska, Izabela P.; Reid, Delyth M.; Wilson, Heather M.; Kuffová, Lucia; Cornall, Richard J.; Forrester, John V. (Frontiers in Immunology, 2020)
We specify the clinical features of a spontaneous experimental autoimmune uveitis (EAU) model, in which foreign hen-egg lysozyme (HEL) is expressed in the retina, controlled by the promoter for interphotoreceptor retinol binding protein (IRBP). We previously reported 100 % P21 (post-partum day) IRBP:HEL single transgenic (sTg) mice, when crossed to transgenic T cell receptor mice (3A9) generating the double transgenic (dTg) genotype, develop EAU despite profound lymphopenia (thymic HEL-specific T cell deletion). In this work, we characterised the immune component of this model and found conventional dTg CD4+ T cells were less anergic than those from 3A9 controls. Furthermore, prior in vitro HEL-activation of 3A9 anergic T cells (Tan) rendered them uveitogenic upon adoptive transfer (Tx) to sTg mice, and antigen-experienced (AgX, dTg), but not naïve (3A9) T cells halted disease in P21 dTg mice. Flow cytometric analysis of the AgX cells elucidated the underlying pathology: FoxP3+CD25hiCD4+ T regulatory cells (Treg) comprised ~18 %, while FR4+CD73+FoxP3-CD25lo/-CD4+ Tan comprised ~1.2 % of total cells. Further Treg-enrichment (~80 %) of the AgX population indicated FoxP3+CD25hiCD4+ Treg played a key role in EAU-suppression while FoxP3-CD25lo/-CD4+ T cells did not. Here we present the novel concept of dual immunological tolerance where spontaneous EAU is due to escape from anergy with consequent failure of Treg induction and subsequent imbalance in the [Treg:Teffector] cell ratio. The reduced numbers of Tan, normally sustaining Treg to prevent autoimmunity, are the trigger for disease, while immune homeostasis can be restored by supplementation with AgX, but not naïve, antigen-specific Treg.